Toxin A–Predominant Pathogenic Clostridioides difficile: A Novel Clinical Phenotype. (11th August 2019) - Lin, Qianyun; Pollock, Nira R; Banz, Alice; Lantz, Aude; Xu, Hua; Gu, Limei; Gerding, Dale N; Garey, Kevin W; Gonzales-Luna, Anne J; Zhao, Mingwei; Song, Linan; Duffy, David C; et al.
Abstract: Background: Most Clostridioides difficile toxinogenic strains produce both toxins A and B (A + B + ), but toxin A–negative, toxin B–positive (A − B + ) variants also cause disease. We report the identification of a series of pathogenic clinical C. difficile isolates that produce high amounts of toxin A with low or nondetectable toxin B. Methods: An ultrasensitive, quantitative immunoassay was used to measure toxins A and B in stool samples from 187 C. difficile infection (CDI) patients and 44 carriers. Isolates were cultured and assessed for in vitro toxin production and in vivo phenotypes (mouse CDI model). Results: There were 7 CDI patients and 6 carriers who had stools with detectable toxin A (TcdA, range 23–17 422 pg/mL; 5.6% of samples overall) but toxin B (TcdB) below the clinical detection limit (<20 pg/mL; median TcdA:B ratio 17.93). Concentrations of toxin A far exceeded B in in vitro cultures of all 12 recovered isolates (median TcdA:B ratio 26). Of 8 toxin A>>B isolates tested in mice, 4 caused diarrhea, and 3 of those 4 caused lethal disease. Ribotyping demonstrated strain diversity. TcdA-predominant samples were also identified at 2 other centers, with similar frequencies (7.5% and 6.8%). Conclusions: We report the discovery of clinical pathogenic C. difficile strains that produce high levels of toxin A but minimal or no toxin B. This pattern of toxin production is not rare (>5% of isolates) and is consistently observed in vitro and in vivo in humans and mice. Our study highlights the significance of toxin A in human CDI pathogenesis and has important implications for CDI diagnosis, treatment, and vaccine development. Abstract : We identified multiple pathogenic clinical isolates of Clostridioides difficile that produced high levels of toxin A but minimal or no toxin B, highlighting the pathogenic significance of toxin A and implications for C. difficile infection diagnoses, treatment, and vaccine development.